Pengembangan Sumber Daya Manusia Melalui Digital Market sebagai Penunjang Percepatan Pertumbuhan Ekonomi Daerah - Novita Wahyu Setyawati; Santi Octavia; Dewi Sri Woelandari (Universitas 45 Surabaya, 2025)
The use of internet-based technology leverages the role of social media as part of the daily need for socializing with other users. Underdeveloped Regions (DRs) are districts whose communities and territories are relatively underdeveloped compared to other regions on a national scale. Therefore, the government has established programs to address this underdevelopment. This study employed qualitative analysis using a SWOT analysis. The results of this study undeniably demonstrate that technology is now significantly helpful in all aspects, even permeating all aspects of human activity. The use of technology in marketing is now highly desirable. MSMEs, SMEs, cooperatives, and micro-businesses in Indonesia have gradually begun utilizing digital marketing as a basis for advertising, information, and product publication for their various business activities. Outreach and training have begun for MSMEs, SMEs, cooperatives, home industries, and small businesses, both family-owned and home-based. Social media is the most widely used tool by the public as a means to operate a home industry. The role of digital marketing in the culinary business can be effectively realized if supported by an understanding of consumer behavior that aligns with the latest technological developments.